Dividend and Profit Allocation Practices of Performing Cooperatives in Malaysia - Nurizah Noordin; Sushila Devi Rajaratnam; Mohd. Shahron Anuar Said; Farahaini Mohd. Hanif; Rafedah Juhan (Oñati Socio-Legal Series)
This paper explores the dividend payout and profit allocation practices of performing cooperatives in Malaysia, specifically how net profits were distributed as between dividends and various funds established for the benefit of members, after the necessary statutory deduction has been made. This paper is an exploratory study that is confined to performing co-operatives throughout Malaysia of different sizes and activities. Figures were derived from the 2008, 2007 and 2006 audited annual financial statements provided by the co-operatives themselves. Overall the study revealed that micro co-operatives are found to have paid the highest average dividend payouts, followed by the large co-operatives. Credit co-operatives which have a sizeable amount of shares and subscriptions are observed to have the lowest average dividend payout ratio. The highest dividend payout is given out by the construction and consumer co-operatives. Besides dividends, co-operatives normally allocate part of their annual net profit for the benefit of members in the form of specific funds for members’ social and related purposes. It was observed that in 2007, all co-operatives have increased their allocation towards members’ benefits except for co-operatives in the services sector. In conclusion, the credit, agriculture and industrial co-operatives are the top three functions with the highest level of contribution to members' benefit fund.